The slow philosophy of J.M. Coetzee - Wilm, Jan 1983- (Bloomsbury, 2017)
"In The Slow Philosophy of J.M. Coetzee Jan Wilm analyses Coetzee's singular aesthetic style which, he argues, provokes the reader to read his works slowly. The effected 'slow reading' is developed into a method specifically geared to analyzing Coetzee's singular oeuvre, and it is shown that his works productively decelerate the reading process only to dynamize the reader's reflexion in a way that may be termed philosophical. Drawing on fresh archival material, this is the first study of its kind to explore Coetzee's writing process as already slow; as a program of seemingly relentless revision which brings forth his uniquely dense and crystalline style. Through the incorporation of material from drafts and notebooks, this study is also the first to combine an exploration of the writer's stylistic choices with a rigorous analysis of the reader's responses. The book includes close readings of Coetzee's popular and lesser known work, including Waiting for the Barbarians, Life & Times of Michael K, Disgrace, Slow Man and The Childhood of Jesus."
Keywords: Coetzee, J. M. / 1940- / Criticism and interpretation; Coetzee, J. M. / 1940-; Coetzee, J. M. -- 1940-; Philosophie